Conversations with The Bedouin and Ansar: An Analysis of Rasulullah's Communication Strategy - Mohd Faizal Kasmani; Muhamad, NAF; Abdullah, R; Jaafar, N; Ghazali, NZM (Natl Univ Malaysia, Fac Social Sciences & Humanities, 2024)
Indexed by Scopus